Development of an Android-Based Financial Management App to Support Educational Infrastructure Enhancement at Pondok Pesantren Nurul Hidayah in Accordance with SDG 9 - Windarto, Windarto; Martini, Martini; Irawan, Yousep Eka (Sebatik, 2024)
Technological advancements have significantly transformed human life, with increasing digitalization across various aspects. However, in the context of the Fourth Industrial Revolution, these advancements have disrupted the role of humans, raising concerns about the potential loss of humanity's essence. In response to these challenges, Japan introduced the concept of Smart Society 5.0 in 2019 to mitigate the negative impacts of this disruption by re-establishing humans as the central element in modern life. As a form of community service, the service team developed the program "Simple Financial Application as a Medium for Financial Management at Nurul Hidayah Islamic Boarding School," located in Sukaharja, Cijeruk, Bogor Regency. The primary issue faced by the partner was the manual nature of financial management, which increased the risk of recording errors and discrepancies in financial data. This activity aimed to digitize the financial administration system and improve the digital literacy of the students and staff at the boarding school through seminars, training, and mentoring. The methods employed included a holistic approach involving observation, interviews, digital financial literacy seminars, training on using Android-based financial applications, and both online and offline mentoring over three months. The results demonstrated an improvement in the partner's ability to use financial technology, enhanced efficiency in recording financial transactions, and increased transparency in fund management. This activity contributed to Nurul Hidayah Islamic Boarding School by strengthening staff capabilities in digital-based financial management and fostering community empowerment through the utilization of technology to achieve sustainable and efficient financial management.